The future of higher education in BRIC countries: a demographic perspective - Guimarães, Raquel Rangel de Meireles (2013)
In regard to the development and reform of higher education (HE), recent and projected evidence suggest that enrollment growth is likely to be slower than it is at present (or even negative) as a result of ageing populations. The case of the BRIC countries is particularly interesting for the study of the impact of demographic changes on HE because these countries show considerable diversity regarding their demographic transition. This paper explores how demographic changes are likely to affect the demand for higher education in BRIC countries. I argue that these countries are now facing a great expansion of enrollment but, given declining fertility levels, diversification of the HE clientele will become a common strategy. But diversification of the student population will place a new and complex set of demands on HE institutions, and equity in higher education in the near future will depend on how HE systems are structured in these countries.